Sistem Informasi Penjualan Pakaian Berbasis Web Pada Toko Kolor Murah Ungaran Menggunakan Metode Waterfall - Tara Indah Afelia; Abdul Rohman (Jurnal Mahasiswa Teknik Informatika, 2022)
Kolor Murah Shop is a pleace that sells clothes used in everyday life, such as negligee, baby doll, suits and shorts. Because Kolor Murah Shop is still in the development stage, this store does not yet have an adequate system to fulfill the process of selling goods to consumers. Therefore, the author makes web-based sales information system at the Kolor Murah Shop.This web-based sales information system aims to help Kolor Murah Shop consumers make purchases online without having to come to the store directly. In addition, this sales information system also makes it easier for the owner to check the goods purchased by the customers.This sales information system will be developed using the Waterfall method, the programming language used is PHP, MySQL database, and using the Notepad++ application as server-side scripting.This research will produce a web-based clothing sales information system at a Kolor Murah Shop and have an appropriate interface design so that it can provide broad information. Based on the results of the black box sytem testing, it produces decent features and usability testing on the questionnaire data produces 84,0%, which means the test results are very feasible and meet the usability aspect.The conclusion that can be drawn from the explanation above is to be able to implement a web-based clothing sales information system at the Kolor Murah Shop Ungaran using the waterfall method.Â Keywords : Waterfall, Notepad++, PHP, MySQL, Toko Kolor Murah.